2012
DOI: 10.1063/1.4772551
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of trap states in unpurified and purified C60 and the influence on organic field-effect transistor performance

Abstract: We investigate trap-state passivation by addition of ultra-low amounts of n-dopants in organic field-effect transistors (OFET) made of as-received and purified fullerene C60. We find a strong dependence of the OFET threshold voltage (VT) on the density of traps present in the layer. In the case of the unpurified material, VT is reduced from 17.9 V to 4.7 V upon trap passivation by a dopant:C60 ratio of ∼10−3, while the Ion/off current ratio remains high. This suggests that ultra-low doping can be used to effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 32 publications
3
65
0
Order By: Relevance
“…Alternatively, the shift of the threshold voltage can also be explained by a filling of traps as proposed by Olthof et al 10 They showed that doping at ultralow concentrations fill traps in the n-type semiconductor C 60 reducing the threshold voltage in these devices while keeping the ON/OFF ratio of the transistor10. Similarly, Naab et al 19 showed that filling of traps in TIPS-pentacene by an n-dopant facilitates a high electron mobility in TIPS-pentacene (6,13-Bis(triisopropylsilylethynyl)pentacene).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the shift of the threshold voltage can also be explained by a filling of traps as proposed by Olthof et al 10 They showed that doping at ultralow concentrations fill traps in the n-type semiconductor C 60 reducing the threshold voltage in these devices while keeping the ON/OFF ratio of the transistor10. Similarly, Naab et al 19 showed that filling of traps in TIPS-pentacene by an n-dopant facilitates a high electron mobility in TIPS-pentacene (6,13-Bis(triisopropylsilylethynyl)pentacene).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, trap filling may be advantageous for OTFT applications where a conductive film is not desired and where trap filling by a dopant has been shown to enhance mobilities and permit control over the threshold voltage. 3134 This attribute of DMBI dopants was exploited in another work, where it was found that TIPS-pentacene can be doped with o -MeO-DMBI to obtain high-mobility n-channel transistors without increasing the bulk conductivity, as is commonly observed when doping organic transistors. 35 …”
Section: Discussionmentioning
confidence: 96%
“…For example, the integer charge transfer model proposed that electron/hole transfer induced polaron states should govern the ELA, and especially control the Fermi level pinning while the substrate work function is higher (or lower) than the ionization potential (or electron affinity (EA)) of organic films [13]. On the other hand, it was pointed out that band-gap states induced by structure defects [14,15] and impurities [16,17] control the Fermi level position in the energy gap of organic films, i.e., the Fermi level will be quasi-pinned at the position near the HOMO if the EA/work function of the substrate is greater than the ionization potential (IP)/work function of the organic film [18,19].…”
Section: Introductionmentioning
confidence: 98%